2015
DOI: 10.1517/14740338.2016.1117605
|View full text |Cite
|
Sign up to set email alerts
|

Tazarotene foam, 0.1%, for the treatment of acne

Abstract: The foam vehicles may increase compliance and satisfaction in some patients and as retinoids are commonly first line acne treatments, this new topical retinoid foam may be a useful option for some acne patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…18 Topical tazarotene as a 0.1% gel, 0.1% cream, or 0.1% foam is therapeutically effective. [19][20][21] A previous study has established the superior efficacy of tazarotene gel, 0.1%, over adapalene, 0.1%, in the management of acne. 22 Tazarotene cream, 0.1%, has been found to significantly improve macular acne scars compared with adapalene gel, 0.3%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 Topical tazarotene as a 0.1% gel, 0.1% cream, or 0.1% foam is therapeutically effective. [19][20][21] A previous study has established the superior efficacy of tazarotene gel, 0.1%, over adapalene, 0.1%, in the management of acne. 22 Tazarotene cream, 0.1%, has been found to significantly improve macular acne scars compared with adapalene gel, 0.3%.…”
Section: Discussionmentioning
confidence: 99%
“…Because few studies have investigated the use of topical retinoids for acne scar management, a comparison evaluating the efficacy of tazarotene and other topical retinoids is not feasible. Moreover, although the evidence for the efficacy of tazarotene application in active acne is robust, 21,23,27,30 the evidence for the efficacy of microneedling therapy is based on studies using fractional radiofrequency microneedling devices. 31,32 Even though study participants show improvement in acne using these devices, it appears that this type of therapy must be continued to maintain the attained outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 A concentração 0,1% é a única aprovada pela FDA, sendo a espuma adequada na acne moderada a severa em idade superior a 12 anos. 37…”
Section: Comedónicaunclassified
“…Some variability in performance and patient acceptability of these conventional topical formulations has been demonstrated. For example, based on their review of the available literature up to 2016, Smith et al [78] concluded that the tazarotene 0.1% foam, that was approved by the FDA in 2012, has increased patient compliance and satisfaction compared to other topical tazarotene formulations.…”
Section: Targeted Topical Delivery Of Retinoids: Strategies To Impmentioning
confidence: 99%